Protocol for a cluster-randomised controlled trial evaluating the impact of a preschool-based capacity building intervention on intimate partner violence and substance misuse in Sri Lanka - Kamalini Lokuge; Polly Wallace; Kalini Subasinghe; Katherine Thurber; Tissa De Silva; Naomi Clarke; Dulshika Waas; Nisansala Liyanage; Udena Attygalle; Bradley Carron-Arthur; Kalyana Rodrigo; Emily Banks; et al. (BMC, 2018)
Abstract Background Past research has identified links between intimate partner violence (IPV) and alcohol misuse and poverty in Sri Lanka. Services that address substance misuse are amongst the few interventions shown to reduce IPV in settings similar to Sri Lanka. This paper describes the protocol for a study examining the impact of a preschool-based capacity building intervention on the prevalence of IPV and substance misuse in parents with children attending preschools, including uptake of available government services. Methods The study is a cluster randomised controlled trial. Government-managed preschools (n = 34) in Galle and Colombo municipalities  will be randomly assigned to an intervention (n = 17) or control group (n = 17). Parents with children attending these preschools will be recruited to participate. The study intervention will build the capacity of selected community volunteers (parents) and preschool teachers in the provision of information and support to families affected by IPV and substance misuse. This intervention is directed at improving uptake, access and coordination of existing services. Data will be collected from all parents, and teachers in the intervention group, pre-intervention and 10 months post-intervention. The primary outcome for this study is experience of IPV amongst mothers of preschool-attending children. Secondary outcomes are substance misuse amongst fathers, measured via the locally adapted Alcohol Use Disorders Identification Test and Drug Abuse Screening Test; and awareness and uptake of services for these issues measured through locally-relevant tools. Demographic information and satisfaction with the intervention will also be assessed. Discussion By intervening through preschools we aim to support high-risk families early enough to arrest the cycle of violence that results in children themselves becoming victims and perpetrators of such violence. The innovative project design will reach the most vulnerable sections of the community and will provide a sustainable and feasible strategy for scale-up of the intervention. Trial registration This study is registered with the Sri Lankan Clinical Trials Registry (2017/038) and has been submitted to ClinicalTrials.gov (U.S National Institutes of Health) under the title "Randomized control trial: preschool-based training and support programs to reduce intimate partner violence (IPV) by addressing alcohol and drug misuse in young families in Sri Lanka"; Registration number: NCT03341455; Registration date: 14 November 2017.